Piling 2020 : proceedings of the Piling 2020 Conference : virtual conference, 23rd-26th March 2021 - Higgins, K. G.; Ainsworth, Y.; Toll, D. G.; Osman, A. S. (ICE Publishing, 2021)
This volume contains the proceedings of the Piling 2020 conference, organised by the British Geotechnical Association (BGA) and supported by the Federation of Piling Specialists (FPS). It brings together the knowledge and experience of industry and academia through detailed research and case histories that provide a definitive and up to date perspective on geotechnical aspects of offshore and onshore piling projects. The papers reflect the themes of the conference which include design of piles and embedded retaining walls, research on piling and piled systems, materials, temporary works, case histories, methods of construction, instrumentation and monitoring, sustainability and digital issues. This collection of papers is of interest to all who work within the broad field of geotechnical engineering, including geotechnical engineers, engineering geologists, piling professionals and academics.